STRATEGI PEMASARAN TELUR AYAM RAS PADA USAHA PETERNAKAN AYAM RAS PETELUR âH. ARIFINâ DI DESA SUNJU KECAMATAN MARAWOLA KABUPATEN SIGI - AS, Irfan Zidni (AGROTEKBIS, 2017)
"H. Arifin" Laying Hen Farming was a laying hen farming located in Sigi Regency. The company had experienced losses due to price declining occurred some time ago, i.e. from a range of Rp 36.000,00-Rp 39.000,00 per rack into Rp 30.000,00-Rp 35.000,00 per rack. Lack of income became more serious because the price declining occurred when feed prices precisely would continue rising. The purpose of this study was to formulate a marketing strategy in accordance with the conditions of external and internal environment of "H. Arifin" Laying Hen Farming. This research was conducted in "H. Arifin" Laying Hen Farming in Sunju Village, Marawola District, Sigi Regency from August to October 2015. The result showed that the marketing strategy in accordance with the conditions of the external and internal environment of "H. Arifin" Laying Hen Farming were the strategies of advertising the product, arranging free delivery service for buyers who purchase in bulk, full fill its production capacity to the maximum, and increase in marketing employees and buying computers. Keywords : Egg, Laying hen.